2021
DOI: 10.1039/d1ra04805h
|View full text |Cite
|
Sign up to set email alerts
|

Naturally based ionic liquids with indole-3-acetate anions and cations derived from cinchona alkaloids

Abstract: The transformation of a plant hormone into an alkaloid-based ionic liquid results in unique changes in physicochemical and biological properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Following recent reports of biologically active ionic liquids (ILs) based on natural compounds and indole-3-butyric acid-based salts, ,, we focused on the synthesis of novel dicationic ionic liquids (DILs) with the IBA anion. Knowing that IBA is poorly soluble in water and that an adjuvant is required to improve the wetting properties and solubility, we used a bis-ammonium cation with two long hydrophobic alkyl chains to obtain compounds with the desired properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following recent reports of biologically active ionic liquids (ILs) based on natural compounds and indole-3-butyric acid-based salts, ,, we focused on the synthesis of novel dicationic ionic liquids (DILs) with the IBA anion. Knowing that IBA is poorly soluble in water and that an adjuvant is required to improve the wetting properties and solubility, we used a bis-ammonium cation with two long hydrophobic alkyl chains to obtain compounds with the desired properties.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been confirmed that the conversion of IBA or IAA to their ionic forms results in these compounds having increased biological activity. 11 Interestingly, introducing a bis-ammonium cation can result in a significantly beneficial modification of physicochemical properties and biological activity than monocationic analogues.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The preparation of ionic liquids bearing a quinine (222a-f, Scheme 39) or a quinidine moiety (224) and (1Hindol-3-yl)acetic acid (indole-3-acetic acid), a naturally occurring plant growth hormone, was reported by Pernak and co-workers in 2021. 90 The readily available quinine 218, a well-known antimalarial cinchona alkaloid, was selectively N-alkylated with six n-alkyl bromides (2-12 carbon atom chains) in DMSO as reported in their previous article. 91 Then, the bromide in salts 219a-f was replaced by the OH anion by means of an ion-exchange resin and the resulting bases 220a-f were neutralized with commercially available indole-3-acetic acid (221) to afford the new ILs 222a-f. Ionic liquid 224 (Scheme 39) containing an N-ethylammonium cation and the same carboxylate anion was also synthesized starting from quinidine 223, another cinchona alkaloid.…”
Section: Miscellaneous Ionic Liquidsmentioning
confidence: 99%
“…Unfortunately, for all the synthetic steps described above, the isolated yields were not reported. The seven ILs were found 90 able to stimulate the growth and development of lettuce ( Lactuca sativa ) as a control plant when compared to pure acid 221 or equimolar mixtures of 221 and quinine 218 . Beside the absence of phytotoxic effects, it was also proven that these ILs were harmless toward several model microorganisms present in the environment.…”
Section: Miscellaneous Ionic Liquidsmentioning
confidence: 99%